PENEGAKAN HUKUM PASAL 112 UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA PADA KASUS TINDAK PIDANA NARKOTIKA DI INDONESIA - Roberts K (Ensiklopedia Education Review, 2023)
Apart from causing multiple interpretations, Article 112 of Law Number 35 of 2009 concerning Narcotics also creates legal uncertainty in its application. In order for the purpose of the law to be achieved, a legal rule is needed that is firm, clear, does not have double meaning, is applied consistently, and is maintained with certainty, the above is called legal certainty. Legal certainty is a feature that cannot be separated from the law itself, especially written law, the law will lose its meaning if it is not accompanied by a legal certainty because the law cannot be used as a guideline for behavior anymore for everyone, in other words there is no law if there is no law. a legal certainty.